Values in the partnership between retainer (Punggawa-Sawi) as a reinforcer in local community of purse seine fishermen in Luwu Regency - Mardiana E Fachry; Alpiani Alpiani; Irwansyah Irwansyah (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
Fishing communities in South Sulawesi are known as Punggawa-Sawi. Numerous researches have shown that the partnership between punggawa-sawi is considered as an â€œexploitationâ€, judging from its profit-sharing system. Purse seine is a Tuna fishing vessel with 5 to 8 sawi and 1 punggawa. The focus of this study is to explain the fishermanâ€™s preference of performing partnership with the punggawa and the values they implement between the work system. There are 8 groups of purse seine fisherman as the sample with a consideration that there were similarities in the pattern of working relationships and fishing activities. This research used qualitative approach and analyzed by descriptive correlation. The results showed that the recruitment of sawi by the punggawa was based on affinity (25%), experience (12,5%), needs for the ship operation (62,5%). The termination of the applicant can be caused by untruthfulness (50%), illness (12,5%), career change (37,5%). The compensation that is originally accepted by the sawi who quits, will be moved to the afflicted ones. The reasons to become sawi is (1) blood relative (20%), assurance of family economic sustainability (65%), and (3). Difficulty to find another job (15%). The profit-sharing system by the retainer is based on 3 reasons, i.e: (1), retainer investment (55%) (2), high risk (30%) and continuing the existing system (20%). Punggawa-sawi fishing communities have strength in the value of social relations that are built on the basis of shared needs (62.5%) and trust (37.5%). The existence of the punggawa-sawi is because of the social security provided to the retainerâ€™s family (87.5%), both in the form of loans and assistance, and the personality of the retainer (12.5%).